LCL Filter design and performance analysis for grid-interconnected systems - Reznik, A.; Simoes, M.; Al-Durra, A.; Muyeen, S.M. (IEEE Industry Applications Society, 2014)
The use of power converters is very important in maximizing the power transfer from renewable energy sources such as wind, solar, or even a hydrogen-based fuel cell to the utility grid. An LCL filter is often used to interconnect an inverter to the utility grid in order to filter the harmonics produced by the inverter. Although there is an extensive amount of literature available describing LCL filters, there has been a gap in providing a systematic design methodology. Furthermore, there has been a lack of a state-space mathematical modeling approach that considers practical cases of delta-and wye-connected capacitors showing their effects on possible grounding alternatives. This paper describes a design methodology of an LCL filter for grid-interconnected inverters along with a comprehensive study of how to mitigate harmonics. The procedures and techniques described in this paper may be used in small-scale renewable energy conversion systems and may be also retrofitted for medium-and large-scale grid-connected systems.